Orthodontıc Surgery In A Skeletal Class I Anterıor Open-Bıte Case. (Case Report) - Enis Güray; Elif Ertaş; Selçuk Basa (Galenos Yayinevi, 1996)
Anterior open-bite cases are considered functionally and aesthetically as a severe syndrome. The treatment planing of skeletal anterior open-bite cases requires elaborated diagnostic and therapeutic implications. In the treatment of such cases, orthodontic treatment alone is not a sufficient therapy and must be associated by the orthognatic surgery. In the present study, the orthodontic and orthognatic treatment of a skeletal Class I case with anterior open-bite were presented and our treatment approach was discussed.